Tectona grandis Seed Mediated Green Synthesis of Silver Nanoparticles and Their Antibacterial Activity - Patel, Snehal; Patel, Narendra (Trends in Sciences, 2023)
Nanobiotechnology is a fast expanding scientific field with potential applications in life sciences and human health care. Silver is a precious metal that occurs naturally, most commonly as a mineral or in combination with other elements. Aqueous T. grandis plant seed extract was utilized in the current investigation as a reducing and capping agent in the biogenesis of silver nanoparticles. Nanoparticles were examined using different techniques like UV-visible spectral analysis, Fourier transform infrared spectra technique, X-ray diffraction technique, and transmission electron microscopy technique. The peak at 429 nm of the surface plasmon resonance by using UV-visible spectra, confirmed the synthesis of nanoparticles. Utilizing Fourier transforms infrared spectral analysis, the explicit functional groups that reduced silver nitrate to create silver nanoparticles in seed extract were found. X-ray diffraction analytical technique was utilized to found the crystalline nature and Face-centered cubic (FCC) configuration of green synthesized silver nanoparticles. Silver nanoparticles with sizes ranging from 32 to 62 nm are visible in images taken using transmission electron microscopy. Using disc diffusion technique, the generated silver nanoparticles showed remarkable antibacterial activity against selected organism, Escherichia coli, Bacillus subtilis, Staphylococcus aureus, and Pseudomonas aeruginosa. AgNPs demonstrated broad spectrum antibacterial action as a result at lower concentrations, and they may provide an effective therapeutic alternative in the future like, development of new antibacterial drugs. This research identified a quick and eco-friendly green synthetic method for producing stable silver nanoparticles. HIGHLIGHTS Preparation of synthesis from selected traditional medicinal plant Tectona grandis Bio synthesis and characterization of silver nanoparticles synthesized using Tectona grandis Seed extract and evaluate its antibacterial activity against selected pathogens The present study established a rapid, economical cheap way of synthesizing silver nanoparticles Synthesized plant mediated nanoparticles can be used against human pathogens acts as antimicrobial drug and have more medicinal applications GRAPHICAL ABSTRACT